2021
DOI: 10.3389/fnhum.2021.653108
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity as a Treatment for Social Anxiety in Clinical and Non-clinical Populations: A Systematic Review and Three Meta-Analyses for Different Study Designs

Abstract: The fear of being in the focus of attention in social situations can develop into a social anxiety disorder (SAD). The classical treatment for SAD is cognitive behavioral therapy, which is in many cases accompanied by drug treatments. A promising alternative treatment is physical activity (PA) interventions, because regular PA has been shown to be suitable for reducing anxiety in general. We conducted a pre-registered systematic review and meta-analysis (PROSPERO registration no. CRD42020191181) as well as two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 113 publications
(190 reference statements)
0
6
0
Order By: Relevance
“…Felipe et al ( 27 ) supported the claim that PA is an evidence-based treatment for depression. Previous research also showed significant associations between a higher level of PA and a lower level of SA symptoms (r = −0.12, p = 0.003) in cross-sectional studies, and PA interventions significantly lower SA symptoms (d = 0–0.22, p = 0.001) in longitudinal studies ( 28 ).…”
Section: Introductionmentioning
confidence: 74%
“…Felipe et al ( 27 ) supported the claim that PA is an evidence-based treatment for depression. Previous research also showed significant associations between a higher level of PA and a lower level of SA symptoms (r = −0.12, p = 0.003) in cross-sectional studies, and PA interventions significantly lower SA symptoms (d = 0–0.22, p = 0.001) in longitudinal studies ( 28 ).…”
Section: Introductionmentioning
confidence: 74%
“…For anxiety disorder, direct and indirect comparisons between AE, RE, MBE, and controls did not show significant differences in treatment effects, but a reduction in anxiety-related symptoms could be observed in every case. Previous meta-analyses also demonstrated little to no benefits in exercise interventions for anxiety disorder [ 170 , 171 ]. Based on the ranking probability plot, RE had the highest probability to be the most effective form of exercise, partly because it increases IGF-1 levels [ 172 ] and reduces inflammation [ 173 ] during training.…”
Section: Discussionmentioning
confidence: 99%
“…A study from 17,550 adolescents found that sports participation predicted lower social anxiety symptoms [12]. Moreover, some researchers con rmed that physical activity can treat clinical social anxiety disorder and reduce social anxiety symptoms in non-clinical samples through systematic review and meta-analyse [13]. Conversely, physical inactivity and sedentary behavior were related to limited social participation, limited contact with neighbors, and higher levels of loneliness [14].…”
Section: Physical Activity and Social Anxietymentioning
confidence: 99%
“…A randomized controlled trial found that the therapeutic effect of high-intensity interval training on social anxiety was twice that of lower intensity training [46] (Plag et al, 2020). In addition, some researchers found that people with more physical activity have lower social anxiety symptoms in crosssectional studies (r = -0.12, P = 0.003), adults after treatment with physical activity were more effective in reducing social anxiety symptoms than children and adolescents in longitudinal studies (d = -0.22, P = 0.001) [13]. What's more, there are some hormone secretion and neurobiological mechanisms that could explain the relationship between physical activity and social anxiety symptoms.…”
Section: The Relationship Between Physical Activity and Social Anxiet...mentioning
confidence: 99%
See 1 more Smart Citation